Perioperative evaluation of the controlling nutritional status (CONUT) score in patients with N0 oral cancer - Miyashita, Hitoshi; Kitamura, Jun; Ando, Fumi; Kouketsu, Atsumu; Kataoka, Yoshihiro; Shimoda, Hajime; Inamura, Naoko; Okamoto, Tomoko; Takahashi, Tetsu (Progress in Nutrition, 2019)
The controlling nutritional status (CONUT) score has been considered to be an established assessment model for evaluating nutrition status in hospital. Here we show the results of perioperative evaluation of the CONUT score in patients with primary N0 oral cancer. The perioperative CONUT score and the prognostic nutritional index (PNI) of total 82 patients undergoing resection for primary oral cancer were analyzed to find the relationship between preoperative nutritional status and postoperative complications or prognosis. We classified these patients into two groups, high CONUT and low CONUT groups, as well as the patients were divided into two groups; low PNI and high PNI groups. 68 cases (82.9%) were divided into low CONUT group, and 14 cases (17.1%) were in high CONUT group. On the other hand, high PNI group has 80 cases (97.6%), and only 2 cases were in low PNI group. Moreover, 12 cases (14.6%) of high PNI were divided into high CONUT group. The CONUT score had a significant relationship with the Body Mass Index (BMI) (P=0.0360). In this study, patients who have a CONUT score of 3 or more are not at increased risk for postoperative complications. Further analyses are required for the evaluation of the complications rate and prognostic significance of the CONUT score in patients with N0 oral cancer.